Sức khỏe, môi trường, tình yêu thương hiệu và quyết định mua sắm: Vai trò của đánh giá trực tuyến - Bùi Thị, Thanh; Trần Trọng, Thùy; Trần Thị Thảo, Trâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The increasing demand for organic personal care products (SPCSHC) is challenging businesses to recognize and respond to changing consumer perceptions, such as health and environmental concerns. This study explores how health consciousness and environmental concerns affect brand love in enhancing purchase decisions in the online reviews context. Using a green marketing theory and a sample of 303 consumers, the research findings show that health consciousness and environmental concerns have a positive impact on brand love. The results also confirm the positive moderating role of online reviews in fostering the relationship between brand love and purchase decisions. As a result, the authors provide relevant implications for managers and academicians in the SPCSHC domain.
Keywords: Health consciousness; Environmental concern; Brand love; Online reviews; Purchase decisions; Green marketing